Global renewable energy transition: A multidisciplinary analysis of emerging computing technologies, socio-economic impacts, and policy imperatives - Herman Zahid; Adil Zulfiqar; Muhammad Adnan; Muhammad Sajid Iqbal; Anwar Shah; Salah Eldeen Gasim Mohamed (Results in Engineering)
The advent of fourth industrial revolution takes along progressive and exponential digital transformation. This study presents an overview of policies, best practices and regional strategies that supports renewable energy adoption around the globe. The transition to 100% renewable energy requires political support, innovation in both technology and policy, and efficient governance. However, it has been analysed through extensive literature review that previous measures have significantly reduced renewable energy costs through technological advancements, market expansion, and economies of scale. To further increase renewable energy adoption across all sectors, financial incentives, concrete support schemes, intervention of advanced computing, market designs and robust business models are essential. Defining clear short and long-term goals for energy system transition is a critical first step, providing the regulatory stability necessary for both public authorities and private operators to ensure a successful transition. This study contributes to the trends, socio-technical perspective, challenges of conventional energy systems and identifying the contemporary digital technologies in the renewable energy transition. The technologies involved in achieving 100% seamless integration of renewable energy in the paradigm of smart grid and super smart grid include cyber-physical systems, Internet of things, metaverse, cloud computing and big data along with the other tools. Energy storage options and hydrogen storage are also discussed in this study and further explored the role of digital technologies in energy storage for an ultimate transition.